2015
DOI: 10.1097/tp.0000000000000570
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Low- Versus High-dose Valganciclovir for Prevention of Cytomegalovirus Disease in High-risk Renal Transplant Recipients

Abstract: Low-dose and high-dose valganciclovir regimens provide similar efficacy in preventing CMV disease in high-risk RTR, with a reduced incidence of leukopenia associated with the low-dose regimen and no difference in resistant CMV. Low-dose valganciclovir may provide a significant cost avoidance benefit.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
50
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(55 citation statements)
references
References 22 publications
4
50
1
Order By: Relevance
“…Gruber et al (11) Acute rejection A total of 6 studies evaluated the AR rate (11)(12)(13)(14)(15)(16). Incidence of AR showed that there was no significant difference between VGC 450 mg and VGC 900 mg (1343 patients, OR 0.77, 95%CI 0.53-1.14, p=0.19; Figure 3).…”
Section: Infectionmentioning
confidence: 99%
See 3 more Smart Citations
“…Gruber et al (11) Acute rejection A total of 6 studies evaluated the AR rate (11)(12)(13)(14)(15)(16). Incidence of AR showed that there was no significant difference between VGC 450 mg and VGC 900 mg (1343 patients, OR 0.77, 95%CI 0.53-1.14, p=0.19; Figure 3).…”
Section: Infectionmentioning
confidence: 99%
“…Three of these studies reported on high-risk RTR (13,14,17). Three studies (12,15,16) reported on moderate-risk RTR, and one study (11) reported on all risk RTR.…”
Section: Study Descriptionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our results suggest that low-dose valganciclovir prophylaxis may have the same effect as a high dose, with favorable economic benefits as concluded from other studies. 45 A formal cost-effective analysis of the data from this study is currently in progress.…”
Section: Study Limitationsmentioning
confidence: 99%